2018
DOI: 10.4103/sni.sni_392_17
|View full text |Cite
|
Sign up to set email alerts
|

Combined microsurgical and endoscopic technique for removal of extensive intracranial epidermoids

Abstract: Background:Intracranial epidermoid tumors are challenging lesions because they grow along the subarachnoid spaces around delicate neurovascular structures and often extend from one compartment to another. The purpose of this study was to determine the usefulness of endoscopic assistance in the microsurgical resection of these lesions, in which total resection is therapy of choice.Methods:A total of 48 cases of intracranial epidermoids were treated by combined microscopic and endoscopic techniques. Initially, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…reported 79% benefit in complete resection of the lesion which is in accordance with the findings of the present study. [ 24 25 26 ] In the current study, the number of cases with multicompartmental spread was more compared to other studies where staged operation was required. Multistage operation with good exposure of the lesion results in lesser recurrence as compared to incomplete exposure in single-stage surgery as demonstrated in many studies.…”
Section: Discussionmentioning
confidence: 66%
“…reported 79% benefit in complete resection of the lesion which is in accordance with the findings of the present study. [ 24 25 26 ] In the current study, the number of cases with multicompartmental spread was more compared to other studies where staged operation was required. Multistage operation with good exposure of the lesion results in lesser recurrence as compared to incomplete exposure in single-stage surgery as demonstrated in many studies.…”
Section: Discussionmentioning
confidence: 66%
“…A recent meta-analysis reported that the recurrence rate of intracranial epidermoid tumors is roughly one in ten patients, and some studies showed no recurrence even after subtotal resection [8]. However, several studies included in that meta-analysis obtained follow-up imaging only when symptoms occurred and did not perform MRI annually, which might make their interpretation problematic [2,19,26]. In the current study, we annually repeated MRI studies to radiologically screen for tumor recurrence, and we found that most STR cases do recur, most recurrences occurring within 2 years of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The objective end of an endoscope is very close to the workpiece and has a sharp convergent light beam. It improves visibility by illuminating the hard-to-access peripheral space of a tumour cavity, improving surgeon satisfaction and patient-based outcomes (Singh et al, 2018;Tammam et al, 2022;Tuchman et al, 2014). An exoscope provides an excellent view to perform superficial dissection and resect surface brain tumours (Kinoshita et al, 2021).…”
Section: Status Of Neuro-endoscopementioning
confidence: 99%